Comportamiento de indicadores reproductivos individuales. II. VacasCriollas de Cuba en Camagüey - de Loyola Oriyés, Carlos Javier; Carlos Oliva Díaz, Roberto; Pérez Lastre, Reynaldo (apm, 2025)
NOTA TÉCNICA